Margarita Salas: a great name for a perfectible postdoctoral contract - Font-Julián, Cristina I.; Orduña-Malea, Enrique (Anuario ThinkEPI, 2023)
One year after the incorporation of Margarita Salas researchers in universities and research centres thanks to the plan for the requalification of the Spanish university system carried out by the Ministry of Universities, this work compiles the main problems and limitations of this postdoctoral contract and outlines some possible solutions for future calls with similar characteristics.
Keywords: Postdoctoral contracts; Young researchers; Spain; Ministry of Universities; Job insecurity; Universities; Science management